Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/s00221-003-1604-4
|View full text |Cite
|
Sign up to set email alerts
|

The source of corticocollicular and corticobulbar projections in area Te1 of the rat

Abstract: Cortical area Te1 in the rat commonly is associated with primary auditory cortex. It is the source of direct projections to the inferior colliculus (IC), superior olivary complex (SOC), and the cochlear nucleus (CN). A question that arises is whether these descending pathways derive from a common source or separate populations of cortical neurons. We addressed this question in seven rats by injecting either Diamidino yellow (DiY) or Fast blue (FB) into the IC and injecting the other tracer into the CN (n=4) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 18 publications
2
68
0
Order By: Relevance
“…The AC to IC projection has been widely studied (Diamond et al, 1969;FitzPatrick and Imig, 1978;Beyerl, 1978;Andersen et al, 1980;Syka, 1984a,b, 2001;Faye-Lund and Osen, 1985;Coleman and Clerici, 1987;Games and Winer, 1988;Herbert et al, 1991;Saldaña et al, 1996;Winer et al, 1998;Prieto and Winer, 1999;Winer and Prieto, 2001;Doucet et al, 2003;Bajo and Moore, 2005;Bajo et al, 2007;Schofield, 2009), and its distribution in the different IC subdivisions is well known. In the rat, anterograde tract tracing with Phaseolus vulgaris leucoagglutinin in the AC suggests higher terminal field density in the DC and LC relative to the CN of the IC (Saldaña et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The AC to IC projection has been widely studied (Diamond et al, 1969;FitzPatrick and Imig, 1978;Beyerl, 1978;Andersen et al, 1980;Syka, 1984a,b, 2001;Faye-Lund and Osen, 1985;Coleman and Clerici, 1987;Games and Winer, 1988;Herbert et al, 1991;Saldaña et al, 1996;Winer et al, 1998;Prieto and Winer, 1999;Winer and Prieto, 2001;Doucet et al, 2003;Bajo and Moore, 2005;Bajo et al, 2007;Schofield, 2009), and its distribution in the different IC subdivisions is well known. In the rat, anterograde tract tracing with Phaseolus vulgaris leucoagglutinin in the AC suggests higher terminal field density in the DC and LC relative to the CN of the IC (Saldaña et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Projections to the thalamus arise in the superficial and deep parts of cortical layer V and throughout layer VI (Winer and Prieto, 2001). In contrast, projections to the IC arise mainly in the middle of layer V (Games and Winer, 1988;Prieto and Winer, 1999;Doucet et al, 2003;Bajo and Moore, 2005;Bajo et al, 2006), where corticothalamic cells are not found (cf. Winer, 2006).…”
Section: Other Potential Sources Of the Bda-labeled Terminals And Axomentioning
confidence: 90%
“…Interactions between top-down modulatory systems and the MOC efferent system are particularly intriguing, yet poorly understood, perhaps because of the frequent use of anesthesia in animal studies. A small percentage of deep layer cortical projection neurons directly target MOC neurons in the ventral nucleus of the trapezoid body (Coomes and Schofield 2004; Feliciano and Potashner 1995), but the more prominent routes from the auditory cortex to the MOC neurons are mediated by polysynaptic projections via the inferior colliculus (Doucet et al 2003;Thompson and Thompson 1993;Vetter et al 1993) or cochlear nucleus (Schofield and Coomes 2005). Direct electrical stimulation of the auditory cortex in awake bats can modulate the cochlear microphonic in a frequencyspecific fashion, suggesting that the anatomical links between the corticofugal and olivocochlear control systems have a functional counterpart as well (Suga et al 2002).…”
Section: The Olivocochlear Reflex Pathway and Its Top-down Modulationmentioning
confidence: 99%